A terminal level analysis of service quality at Nigerian seaports - Daniel Sakyi; Christian Kwarteng Appiah; Enock Kojo Ayesu; Mustapha Immurana; Samuel Tawiah Baidoo (Journal of Shipping and Trade (JST), 2020)
Seaport terminals are major facilitators of international trade. One issue that is very crucial to the performance and survival of seaport terminals is the quality of service provided. However, in order to enhance the quality of service provided at these terminals, it is important to know customers' expectations and perceptions about service quality. Notwithstanding, very little is known about customers' expectations and perceptions on the service quality of seaport terminals in Africa. This paper therefore provides a comparative analysis of service quality of Nigerian seaport terminals with the aid of the gap score technique of the service quality (SERVQUAL) model. It is found that generally, all the selected terminals studied have low service quality. With regard to the average gap score per service quality dimension for all the selected terminals, transparency has the best service quality (least gap score) whiles responsiveness has the least service quality (highest gap score). The implication is that, in seaport terminals quest to enhance service quality, more attention should be paid towards enhancing responsiveness by providing prompt services, helping customers and informing them when exactly services will be performed.
Keywords: F10; L25; M11; 650; Trade facilitation; Service quality; Seaport terminals competitiveness; Nigeria